Physical investigations on NiMn2O4 sprayed magnetic spinel for sensitivity applications - YUMAK YAHŞİ, AYŞE (ELSEVIER, 2015)
NiMn2O4 ternary nickel manganese oxide thin films spinets have been grown on glass substrates at 350 degrees C through spray pyrolysis technique. X-ray diffraction and Raman spectroscopy analyses show that the synthesized film has mainly cubic spinet structure with a preferred orientation along (111) plane. Some optical constants such as the refractive index (n), extinction coefficient (k). Urbach energy (E-U = 342 eV) and optical energy band gap (E-g = 1.07 eV) have been calculated from reflection-transmission spectra. The mirage effect technique has been used to estimate the thermal conductivity (K-c). Its value is K-c =25 W m(-1) K-1. The real part of the ac the conductivity behaviour has been investigated in the frequency range 100 Hz to 1 MHz. It was found that the real conductivity follows a power law (A omega(5)). The dc conductivity has been studied in the temperature range from 250 degrees C to 375 degrees C and supports the variable range hopping model proposed by Mott. The activation energy value estimated from the relaxation frequency is Ea 032 eV. Moreover, the temperature dependency Idle resistance indicates that conduction was well described by a variable range hopping model, in which electron transfer takes place between Mn3+ and Mn4+ ions. (C) 2015 Elsevier B.V. All lights reserved
Keywords: NiMn2O4; Spray pyrolysis; Optical properties; Thermal conductivity; Impedance spectroscopy; Ferromagnetic inverse spinel structure; ELECTRICAL-PROPERTIES; OPTICAL-PROPERTIES; TEMPERATURE; FILMS